BIBLIOTECA „OVIDIUS” – PARTENER DE ÎNCREDERE ÎN FORMAREA INTELECTUALĂ A TINERILOR - CIOBANU, director, Filiala „Ovidius”, Liuba (BIBLIOPOLIS, 2020)
The partnership with vocational education schools is a priority of the Ovidius branch. This partnership has opened new perspective of development, with bilateral benefit: space for observation, knowledge, development for each student, a space of self-improving through cultural values and show the acquired abilities. The library became for library partners an information, education, cultural center, offering the possibility to communicate with writers, musicians, singers, actors, painters, scientists, politicians, athletes in an informal intimate atmosphere. The partnership with these institutions is based on loyalty, collaboration, communication and human solidarity.